Disrupting the Market in Bodily Data Through Data Decommodification - Tusikov, Natasha (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
Pervasive tracking of people and the wholesale capture of their data are foundational elements of the data economy. This article explores what opposition to the normalisation of surveillance and commodification of data might entail, with a focus on period-tracking apps, which enable users to monitor their menstrual cycles and identify fertile timeframes to manage pregnancy and symptoms related to menstruation. The article is guided by the following questions: how do period-tracking apps commodify users’ bodily data and how might data decommodification be a response to the harms from period-tracking apps’ data-intensive business models? Designed to make a theoretical intervention and taking a political economy approach, the article develops the concept of data decommodification from Karl Polanyi’s (2001) concept of fictitious commodities. To explore data decommodification, the article comparatively assesses two period-tracking apps, the UK-headquartered Flo Health and the Germany-based Clue, with a focus on their data practices in the United States and European Union, respectively. Data decommodification demands a new set of social relations and government responsibilities in the data economy, including privacy and data protection, the restriction of apps’ trade in health data by regulators, and the prohibition of the commercial trade in health data.